Increasing temperature-driven changes in life history traits and gene expression of an Antarctic tardigrade species - Giovannini, Ilaria; Manfrin, Chiara; Greco, Samuele; Vincenzi, Joel; Altiero, Tiziana; Guidetti, Roberto; Giulianini, Piero; Rebecchi, Lorena (Frontiers in Physiology, 2023)
The Antarctic region has been experiencing some of the planet's strongest climatic changes, including an expected increase of the land temperature. The potential effects of this warming trend will lead ecosystems to a risk of losing biodiversity. Antarctic mosses and lichens host different microbial groups, micro-arthropods and meiofaunal organisms (e.g. tardigrades, rotifers). The eutardigrade Acutuncus antarcticus is considered a model animal to study the effect of increasing temperature due to global warming on Antarctic terrestrial communities. In this study, life history traits and fitness of this species are analyzed by rearing specimens at two different and increasing temperatures (5 °C vs 15 °C). Moreover, the first transcriptome analysis onf Acutuncus antarcticus is performed, exposing adult animals to a gradual increase of temperature (5, 10, 15, and 20 °C) to find differentially expressed genes under short-(1 day) and long-term (15 days) heat stress. Acutuncus antarcticus specimens reared at 5 °C live longer (maximum life span: 686 days), reach sexual maturity later, lay more eggs (which hatch in longer time and in lower percentage) compared with animals reared at 15 °C. The fitness decreases in animals belonging to the second generation at both rearing temperatures. The short-term heat exposure leads to significant changes at transcriptomic level, with 67 differentially expressed genes. Of these, 23 upregulated genes suggest alterations of mitochondrial activity and oxido-reductive processes, and two intrinsically disordered protein genes confirm their role to cope with heat stress. The long-term exposure induces alterations limited to 14 genes, and only one annotated gene is upregulated in response to both heat stresses. The decline in transcriptomic response after a long-term exposure indicates that the changes observed in the short-term are likely due to an acclimation response. Therefore, A. antarcticus could be able to cope with increasing temperature over time, including the future conditions imposed by global climate change.